Effects of bone marrow stromal cell transplantation through CSF on the subacute and chronic spinal cord injury in rats. - Norihiko Nakano (PLoS ONE, 2013)
It has been demonstrated that the infusion of bone marrow stromal cells (BMSCs) through the cerebrospinal fluid (CSF) has beneficial effects on acute spinal cord injury (SCI) in rats. The present study examined whether BMSC infusion into the CSF is effective for subacute (1- and 2-week post-injury), and/or chronic (4-week post-injury) SCI in rats. The spinal cord was contused by dropping a weight at the thoracic 8-9 levels. BMSCs cultured from GFP-transgenic rats of the same strain were injected three times (once weekly) into the CSF through the fourth ventricle, beginning at 1, 2 and 4 weeks post-injury. At 4 weeks after initial injection, the average BBB score for locomotor assessment increased from 1.0-3.5 points before injection to 9.0-10.9 points in the BMSC-injection subgroups, while, in the PBS (vehicle)-injection subgroups, it increased only from 0.5-4.0 points before injection to 3.0-5.1 points. Numerous axons associated with Schwann cells extended longitudinally through the connective tissue matrices in the astrocyte-devoid lesion without being blocked at either the rostral or the caudal borders in the BMSC-injection subgroups. A small number of BMSCs were found to survive within the spinal cord lesion in SCI of the 1-week post-injury at 2 days of injection, but none at 7 days. No BMSCs were found in the spinal cord lesion at 2 days or at 7 days in the SCI of the 2-week and the 4-week post-injury groups. In an in vitro experiment, BMSC-injected CSF promoted the survival and the neurite extension of cultured neurons more effectively than did the PBS-injected CSF. These results indicate that BMSCs had beneficial effects on locomotor improvement as well as on axonal regeneration in both subacute and chronic SCI rats, and the results also suggest that BMSCs might function as neurotrophic sources via the CSF.